2014
DOI: 10.1111/mpp.12181
|View full text |Cite
|
Sign up to set email alerts
|

The response regulator BcSkn7 is required for vegetative differentiation and adaptation to oxidative and osmotic stresses in Botrytis cinerea

Abstract: The high-osmolarity glycerol pathway plays an important role in the responses of fungi to various environmental stresses. Saccharomyces cerevisiae Skn7 is a response regulator in the high-osmolarity glycerol pathway, which regulates the oxidative stress response, cell cycle and cell wall biosynthesis. In this study, we characterized an Skn7 orthologue BcSkn7 in Botrytis cinerea. BcSKN7 can partly restore the growth defects of S. cerevisiae SKN7 mutant and vice versa. The BcSKN7 mutant (ΔBcSkn7-1) revealed incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 74 publications
3
31
1
Order By: Relevance
“…A comparison of the results shows that there are several differences between the phenotypes of the ⌬bcskn7 mutants, starting with a divergent gene annotation. In contrast to six introns confirmed by cDNA sequencing in the ORF of bcskn7 in this study, only four introns are described in Yang et al (32). Moreover, the results concerning formation of reproductive structures, sensitivity to cell wall stress, and virulence differ.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…A comparison of the results shows that there are several differences between the phenotypes of the ⌬bcskn7 mutants, starting with a divergent gene annotation. In contrast to six introns confirmed by cDNA sequencing in the ORF of bcskn7 in this study, only four introns are described in Yang et al (32). Moreover, the results concerning formation of reproductive structures, sensitivity to cell wall stress, and virulence differ.…”
Section: Discussioncontrasting
confidence: 43%
“…Therefore, an additional effector pathway for Bos1 is assumed (26). This pathway probably involves the second response regulator BcSkn7, which was recently identified and partly characterized in a parallel investigation (32). It was shown that under osmotic stress BcSkn7 positively regulated phosphorylation of BcSak1; however, phosphorylation and expression analyses showed that regulation of the oxidative stress response probably is independent of BcSak1 phosphorylation, in a similar manner to that observed in yeast.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…We also found that the ⌬MrSkn7 mutant completely lost the ability to produce conidia on PDA, while the conidiation abilities were only partially impaired in the BcSkn7 deletion mutant of B. cinerea (9), ⌬FgSkn7 mutant of F. graminearum (8), and ⌬SrrA (i.e., ⌬AnSkn7) mutant of A. nidulans (36). Salt stress could induce the upregulation of sporulation-related genes (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The orthologs of Skn7 in yeasts and different filamentous fungi generally contribute to cell wall integrity, sporulation, osmotic stress, and oxidative stress (5). Interestingly, deletion of MoSkn7 (Magnaporthe oryzae Skn7) in M. oryzae (7), FgSkn7 (Fusarium graminearum Skn7) in F. graminearum (8), and BcSkn7 (Botrytis cinerea Skn7) in B. cinerea (9) did not impair fungal virulence and thereby the ability to infect their respective plant hosts. In contrast, AaSkn7 (Alternaria alternata Skn7) is required by A. alternata to infect citrus (10).…”
mentioning
confidence: 99%